Papillary neoplasias of the biliary tract - Resende,Vivian (2014)
The authors conducted a revisional study of intraepithelial papillary lesions of the bile ducts, characterized by being a kind of rare, intraductal growing cholangiocarcinoma. Articles published in the last 10 years were reviewed. The authors considered that the adenoma-carcinoma development is an important feature to warrant prophylactic measures through excisions. The histological type and biomolecular behavior may have relevance in the postoperative course of such lesions, which have a better prognosis when compared with other histological types.